2006
DOI: 10.3852/mycologia.98.4.550
|View full text |Cite
|
Sign up to set email alerts
|

New findings of Neurospora in Europe and comparisons of diversity in temperate climates on continental scales

Abstract: The life cycles of the conidiating species of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 19 publications
0
36
0
1
Order By: Relevance
“…Fungal spore killers were fi rst discovered in Neurospora among natural populations of N. sitophila (Sk-1) and N. intermedia (Sk-2 and Sk-3). Sk-2 and Sk-3 have been found in only four N. intermedia isolates from Borneo (Brunei, Sabah), Java and Papua New Guinea among ~2500 isolates of this species from around the world, whereas Sk-1 killer is found in up to 30% of N. sitophila isolates from many parts of the world (Turner and Perkins 1979;Turner 2001;Jacobson et al 2006).…”
Section: Spore Killers As Meiotic Drive Elementsmentioning
confidence: 96%
See 1 more Smart Citation
“…Fungal spore killers were fi rst discovered in Neurospora among natural populations of N. sitophila (Sk-1) and N. intermedia (Sk-2 and Sk-3). Sk-2 and Sk-3 have been found in only four N. intermedia isolates from Borneo (Brunei, Sabah), Java and Papua New Guinea among ~2500 isolates of this species from around the world, whereas Sk-1 killer is found in up to 30% of N. sitophila isolates from many parts of the world (Turner and Perkins 1979;Turner 2001;Jacobson et al 2006).…”
Section: Spore Killers As Meiotic Drive Elementsmentioning
confidence: 96%
“…More recent collections in the temperate regions of North America and Europe following forest fi res, however, gave a different population structure: N. discreta, N. crassa and N. sitophila were more common than N. intermedia. Subsequent analyses of wild strains provided insights into the diversity and evolution of this model organism (Jacobson et al 2004(Jacobson et al , 2006. To this day, the wild isolates continue to serve as a valuable resource and studies with them have contributed to several major discoveries: vegetative incompatibility genes, transposable elements, senescence-causing mitochondrial plasmids, recessive sexual phase mutants and meiotic driveinducing spore killers, to name a few.…”
Section: Natural Populationsmentioning
confidence: 99%
“…One isolate from Europe (10866 Italy), however associated with clade A (predominantly representing isolates from the Caribbean Basin and the Ivory Coast; Jacobson et al, 2006). An explanation for this exception may be that isolate 10866 was at some time in history transported from the Caribbean Basin or Ivory Coast to Europe (e.g., by human trade).…”
Section: Resultsmentioning
confidence: 99%
“…Refl ecting the natural distribution of species, the FGSC collection holds 279 wild-type N. crassa isolates, 611 N. intermedia isolates, 193 N. tetrasperma isolates, 152 N. discreta isolates, 246 N. sitophila isolates and 12 isolates of other Neurospora species. Recent studies have shown that Neurospora can be found in temperate zones including the US and several countries in Europe (Jacobson et al 2006), and many of these temperate isolates have also been deposited in the FGSC collection. The wild strains in the FGSC collection have been used in genome sequencing efforts (table 2), and have allowed the identifi cation of the only transposon ever found in Neurospora (Sewell and Kinsey 1996).…”
Section: Fgsc Holdingsmentioning
confidence: 99%